Evidence That Vesicles Undergo Compound Fusion on the Synaptic Ribbon - Matthews, Gary (Society for Neuroscience, 2008)
The ribbon synapse can release a stream of transmitter quanta at very high rates. Although the ribbon tethers numerous vesicles near the presynaptic membrane, most of the tethered vesicles are held at a considerable distance from the plasma membrane. Therefore, it remains unclear how their contents are released. We evoked prolonged bouts of exocytosis from a retinal bipolar cell, fixed within seconds, and then studied the ribbons by electron microscopy. Vesicle density on ribbons was reduced by ∼50% compared with cells where exocytosis was blocked with intracellular ATP-γS. Large, irregularly shaped vesicles appeared on the ribbon in cells fixed during repetitive stimulation of exocytosis, and in some cases the large vesicles could be traced in adjacent sections to cisternae open to the medium. The large cisternal structures were attached to the ribbon by filaments similar to those that tether synaptic vesicles to the ribbon, and they occupied the base of the ribbon near the plasma membrane, where normal synaptic vesicles are found in resting cells. We suggest that the cisternae attached to ribbons represent synaptic vesicles that fused by compound exocytosis during strong repetitive stimulation and, thus, that vesicles tethered to the ribbon can empty their contents by fusing to other vesicles docked at the presynaptic membrane. Such compound fusion could explain the extremely high release rates and the multivesicular release reported for auditory and visual ribbon synapses.